2012
DOI: 10.1021/nn302329c
|View full text |Cite
|
Sign up to set email alerts
|

Micropatterning Thermoplasmonic Gold Nanoarrays To Manipulate Cell Adhesion

Abstract: The ability to reversibly control the interactions between the extracellular matrix (ECM) and cell surface receptors such as integrins would allow one to investigate reciprocal signaling circuits between cells and their surrounding environment. Engineering microstructured culture substrates functionalized with switchable molecules remains the most adopted strategy to manipulate surface adhesive properties, although these systems exhibit limited reversibility and require sophisticated preparation procedures. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
72
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 33 publications
0
72
0
Order By: Relevance
“…Over the past decade, the photothermal effect has been a fertile ground for fundamentally new scientific research. Among the various inorganic (e.g., metal and carbon nanomaterials) and organic (e.g., indocyanine green and polyaniline) photothermal agents, gold nanoparticles and graphene have attracted particular attention due to their high photothermal conversion efficiency as well as their NIR-absorbing spectra, which make them extraordinarily popular in biological applications [277][278][279][280]. Remote manipulation of LCs through the photothermal effects induced by particular nanomaterials is an emerging field of promising materials [281][282][283][284][285].…”
Section: Photonic Applicationsmentioning
confidence: 99%
“…Over the past decade, the photothermal effect has been a fertile ground for fundamentally new scientific research. Among the various inorganic (e.g., metal and carbon nanomaterials) and organic (e.g., indocyanine green and polyaniline) photothermal agents, gold nanoparticles and graphene have attracted particular attention due to their high photothermal conversion efficiency as well as their NIR-absorbing spectra, which make them extraordinarily popular in biological applications [277][278][279][280]. Remote manipulation of LCs through the photothermal effects induced by particular nanomaterials is an emerging field of promising materials [281][282][283][284][285].…”
Section: Photonic Applicationsmentioning
confidence: 99%
“…Thermo-plasmonics [104][105][106][107] is based on the thermal heating originated by the optically resonant excitation of plasmons in nanoparticles. [108][109][110] Localized surface plasmons (LSPs), i.e., plasmon modes in nanostructures, notably enhance the local electric field near the surface of the nanostructures, so as to achieve an enhanced optical response.…”
Section: © 2017 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%
“…3A). Zhu et al [42] reported a protocol to fabricate biofunctionalized micropatterned gold nanoarrays that support integrin-mediated cell adhesion and function as plasmonic nanostoves to physically block and orient the formation of focal adhesion sites and the subsequent cell polarization and migration. Being reversible and not restricted spatiotemporally, thermoplasmonic approaches will open new opportunities to further study the complex interactions between ECM and cells (Fig.…”
Section: Thermoresponsive Surfacesmentioning
confidence: 99%